Human Epidermal Zinc Concentrations after Topical Application of ZnO Nanoparticles in Sunscreens - Zahra Khabir (MDPI AG, 2021)
Zinc oxide nanoparticle (ZnO NP)-based sunscreens are generally considered safe because the ZnO NPs do not penetrate through the outermost layer of the skin, the stratum corneum (SC). However, cytotoxicity of zinc ions in the viable epidermis (VE) after dissolution from ZnO NP and penetration into the VE is ill-defined. We therefore quantified the relative concentrations of endogenous and exogenous Zn using a rare stable zinc-67 isotope (67Zn) ZnO NP sunscreen applied to excised human skin and the cytotoxicity of human keratinocytes (HaCaT) using multiphoton microscopy, zinc-selective fluorescent sensing, and a laser-ablation inductively coupled plasma–mass spectrometry (LA-ICP-MS) methodology. Multiphoton microscopy with second harmonic generation imaging showed that 67ZnO NPs were retained on the surface or within the superficial layers of the SC. Zn fluorescence sensing revealed higher levels of labile and intracellular zinc in both the SC and VE relative to untreated skin, confirming that dissolved zinc species permeated across the SC into the VE as ionic Zn and significantly not as ZnO NPs. Importantly, the LA-ICP-MS estimated exogenous 67Zn concentrations in the VE of 1.0 ± 0.3 μg/mL are much lower than that estimated for endogenous VE zinc of 4.3 ± 0.7 μg/mL. Furthermore, their combined total zinc concentrations in the VE are much lower than the exogenous zinc concentration of 21 to 31 μg/mL causing VE cytotoxicity, as defined by the half-maximal inhibitory concentration of exogenous 67Zn found in human keratinocytes (HaCaT). This speaks strongly for the safety of ZnO NP sunscreens applied to intact human skin and the associated recent US FDA guidance.